Farm Level Analysis of Risk and Risk Management Strategies and Policies Technical Note - Kimura, Shingo (OECD Food, Agriculture and Fisheries Papers, 2011)
This Working Paper serves as a technical background note for the Farm-level analysis of risk, risk management strategies and policies (OECD Food, Agriculture and Fisheries Working Papers No.26). It describes: 1) the data source and analytical methods employed to measure risk exposure at the farm level; 2) the stochastic simulation model to analyze farm behaviour and policy performance under risk; and 3) cluster analysis as a way of selecting representative farms for model calibration